Odpowiedzi

  • nos
  • Początkujący
2010-02-15T19:27:14+01:00
-3x+5(2x-7)-6(-5x+6)= dla x= -1
-3x+10x-35+30x-36=37x-71=-37-71=-108

5(a-2b)+4(3a+6b)+12= dla a= 2 i b = -5
5a-10b+12a+24b+12=17a+14b+12=34-70+12=-24

-(-4xy+3y-2)+7(2xy-x+2y)-(6x+9)= dla x=3 i y= -2
4xy-3y-2+14xy-7x+14y-6x-9=-13x+18xy+11y-11=-39-108-22-11=-180
Najlepsza Odpowiedź!
2010-02-15T19:27:59+01:00
A)-3x+5(2x-7)-6(-5x+6)=-3x+10x-35+30x-36=37x-71=37*(-1) -71=-108
b)5(a-2b)+4(3a+6b)+12=5a-10b+12a+24b+12=17a+14b+12=17*2+14*(-5)+12=34-70+12=-24
c) -(-4xy+3y-2)+7(2xy-x+2y)-(6x+9)=4xy-3y+2+14xy-7x+14y=18xy+11y-7x+2=18*3*(-2)+11*(-2)-7*3+2=-108-22-21+2=-149